TLS: traffic load based scheduling protocol for wireless sensor networks. (2019) - Sahoo, Prasan Kumar; Thakkar, Hiren Kumar
In wireless sensor networks (WSNs), nodes are usually deployed in the monitoring region randomly and densely and are supposed to monitor the region for a longer duration. These sensors are normally powered by a battery and therefore it is essential to regulate the power utilisation of the nodes efficiently. Although most of the current protocols reduce the power utilisation by regulating the sleep and wake-up schedules, they fail to make an adaptive sleep or wake up schedule for the nodes based on their traffic load. This paper proposes a traffic load based adaptive node scheduling protocol to determine the active and sleep schedules of the nodes. The entire network is partitioned into a set of virtual zones and a routing path selection algorithm is proposed considering the residual power of the next hop nodes. Simulation results show that the energy consumption and packet overhead of our protocol are considerably less as compared to similar quorum-based medium access control (MAC) protocols.